2003
DOI: 10.1038/nrc1075
|View full text |Cite
|
Sign up to set email alerts
|

Tumour-cell invasion and migration: diversity and escape mechanisms

Abstract: Cancer cells possess a broad spectrum of migration and invasion mechanisms. These include both individual and collective cell-migration strategies. Cancer therapeutics that are designed to target adhesion receptors or proteases have not proven to be effective in slowing tumour progression in clinical trials--this might be due to the fact that cancer cells can modify their migration mechanisms in response to different conditions. Learning more about the cellular and molecular basis of these different migration/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

47
2,617
2
36

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 2,828 publications
(2,702 citation statements)
references
References 141 publications
47
2,617
2
36
Order By: Relevance
“…Cells extend protrusions with lamellipodia or filopodia to initiate extracellular matrix (ECM) recognition and binding to ECM, which are the prerequisites for the onset of cell motility. 41 The extended projected area of A549R0-LAMC2 cells in our biophysical assay may be the result of LAMC2-induced cell protrusion and contractile force, which are required for cell motility. Moreover LAMC2 IHC of lung ADC TMA showed that LAMC2 was predominant in tumor cells at the boundary between tumor and stroma, further supporting a role of LAMC2 in tumor cell spreading.…”
Section: Discussionmentioning
confidence: 89%
“…Cells extend protrusions with lamellipodia or filopodia to initiate extracellular matrix (ECM) recognition and binding to ECM, which are the prerequisites for the onset of cell motility. 41 The extended projected area of A549R0-LAMC2 cells in our biophysical assay may be the result of LAMC2-induced cell protrusion and contractile force, which are required for cell motility. Moreover LAMC2 IHC of lung ADC TMA showed that LAMC2 was predominant in tumor cells at the boundary between tumor and stroma, further supporting a role of LAMC2 in tumor cell spreading.…”
Section: Discussionmentioning
confidence: 89%
“…Re-expression of active merlin suppresses MM cell invasion, spreading and motility Increased cell motility and invasiveness in vitro is thought to correlate with an enhanced malignant and invasive phenotype in vivo (Friedl and Wolf, 2003). As MMs are highly aggressive and invasive tumors, we investigated the effects of re-expressing merlin in two MM cell lines (Meso17, Meso25) that lack expression of endogenous NF2.…”
Section: Resultsmentioning
confidence: 99%
“…1 Migration and invasion of tumor cells is considerably facilitated (but not entirely dependent) by the expression of proteases digesting the extracellular matrix. 27 For glioblastomas, matrix metalloproteinases (MMP) and few serine proteases have drawn most attention. 28 Secreted MMP-2 (gelatinase A), MMP-9 (gelatinase B), urokinase and other secreted proteases, as well as cell-surface proteases involved in their activation like MT1-MMP or MT2-MMP (membrane type matrix metalloproteinases-1 and -2) seem to play a critical role in this migratory process.…”
Section: Discussionmentioning
confidence: 99%